The influence of the electroneutrality of the metal layer on the plasmon spectrum in "dielectric-metal-dielectric" structures - Polovyi, Vitalii; Petro, Kostrobiy (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
This paper proposes a model that takes into account the discretization of the Fermi wave vector and energy levels, as well as the condition of electroneutrality when investigating the influence of metal thickness on the spectrum of SPPs waves in heterogeneous dielectric-metal-dielectric structures.